2020
DOI: 10.1177/1043659620952524
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Quality of Life, and End of Life Among Indigenous Peoples: A Scoping Review

Abstract: Introduction: While spirituality and quality of life (QOL) are essential components of end-of-life (EOL) care, limited studies have examined these constructs for indigenous peoples. Therefore, the purpose of this article was to examine the state of the science regarding spirituality and QOL at EOL for indigenous people, particularly Native Americans. Method: The Arksey and O’Malley (2005) framework guided this scoping review, which examined 30 articles that included qualitative and quantitative studies, commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…This theme includes empirical results related to Indigenous Elders, patients' and families' perspectives on death and dying, and the characteristics needed for good palliative care. While acknowledging the diversity of Indigenous worldviews, a majority of studies showed that death and dying translate into a non‐linear holistic and natural life process that begins at birth (Colclough & Brown, 2019; Dennis & Washington, 2018; Duggleby et al, 2015; Gebauer et al, 2016; Gott et al, 2017, 2019; Isaacson & Lynch, 2018; Moeke‐Maxwell et al, 2018, 2020; Terpstra et al, 2021). Moeke‐Maxwell et al (2018) describe death and dying as “the idea of the spirit transitioning between the metaphysical and physical realms” (p. 32).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This theme includes empirical results related to Indigenous Elders, patients' and families' perspectives on death and dying, and the characteristics needed for good palliative care. While acknowledging the diversity of Indigenous worldviews, a majority of studies showed that death and dying translate into a non‐linear holistic and natural life process that begins at birth (Colclough & Brown, 2019; Dennis & Washington, 2018; Duggleby et al, 2015; Gebauer et al, 2016; Gott et al, 2017, 2019; Isaacson & Lynch, 2018; Moeke‐Maxwell et al, 2018, 2020; Terpstra et al, 2021). Moeke‐Maxwell et al (2018) describe death and dying as “the idea of the spirit transitioning between the metaphysical and physical realms” (p. 32).…”
Section: Resultsmentioning
confidence: 99%
“…Family involvement in decision‐making constitutes a central value underpinning culturally responsive palliative care among Indigenous peoples (Colclough & Brown, 2019; Dennis & Washington, 2018; Duggleby et al, 2015; Galloway et al, 2020; Gebauer et al, 2016; Gott et al, 2019; Isaacson & Lynch, 2018; Moeke‐Maxwell et al, 2020; Terpstra et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sivertsen et al ( 2020 ) explored the relationship between spirituality and coping in Aboriginal people, and identified that an individual's spiritual well‐being includes the connection between the person, family and community. According to Terpstra et al ( 2021 ), spirituality is perceived uniquely within Indigenous populations and is closely linked with their overall quality of life. Given that spirituality is considered a powerful determinant of health for Indigenous populations, more depth in understanding is required to meaningfully integrate spirituality in health‐care programs for Indigenous people (Harrington, 2016 ; Sivertsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%